A review of Opalimosina Roháček, 1983 (Diptera, Sphaeroceridae) from China with new records and two new species - Cao, Wenqiang; Yang, Ding; Dong, Hui (Zootaxa, 2024)
The ten species of Opalimosina Roháček now known from China are reviewed and keyed including two new species, O. aculeata sp. nov. and O. setifera sp. nov., and two newly recorded species O. calcarifera (Roháček, 1975) and O. spathulata Hayashi, 2010.